Analysis of Hazardous and Toxic Waste Management (B3) from the Perspective of Safety, Health, Productivity and Waste Minimization at PT X - Munfarida, Arifati; Hadiyanto, Hadiyanto; Yulianto, Bambang (PT FORMOSA CENDEKIA GLOBAL, 2024)
The management of Hazardous and Toxic Waste (B3) must be carried out by waste producers. PT X as a producer of B3 waste in its production process uses palm oil raw materials and other auxiliary materials. Producers carry out management in accordance with applicable regulations. Waste management can be seen from the perspective of safety, health, productivity and waste minimization. The purpose of this study is to analyze the management of B3 Waste from the perspective of safety, health, productivity and minimization. Data was obtained from surveys and interviews. Analysis method used in statistics. The results of the study showed that 97% strongly agreed with safety, 93% health, 99% productivity and 96% waste initiation.